A Rapid Growth-Independent Antibiotic Resistance Detection Test by SYBR Green/Propidium Iodide Viability Assay - Feng, Jie; Yee, Rebecca; Zhang, Shuo; Tian, Lili; Shi, Wanliang; Zhang, Wen-Hong; Zhang, Ying (Frontiers in Medicine, 2018)
Antibiotic resistant bacteria have caused huge concerns and demand innovative approaches for their prompt detection. Current antibiotic susceptibility tests (AST) rely on the growth of the organisms which takes 1-2 days for fast growing organisms and several weeks for slow growing organisms. Here we show for the first time the utility of the SYBR Green I/Propidium Iodide (PI) viability assay for rapidly identifying antibiotic resistance in less than 30 minutes for major, antibiotic-resistant, fast growing bacteria such as S. aureus, E. coli, K. pneumoniae, and A. baumannii for bactericidal and bacteriostatic agents and in 16 hours for extremely rapid detection of drug resistance for isoniazid and pyrazinamide in slow growing M. tuberculosis. The SYBR Green I/PI assay generated rapid and robust results in concordance with traditional AST methods. This novel growth-independent methodology changes the concept of the current growth-based AST and may revolutionize current drug susceptibility testing for all cells of prokaryotic and eukaryotic origin, and, subject to further clinical validation, may play a major role in saving lives and improving patient outcomes.